Immune thrombotic thrombocytopenic purpura and diabetic ketoacidosis: a case report and literature review - Bai, Geng-Hao; Lin, Mei-Hwa; Chen, Yu-Pei; Chang, Tien-Jyun; Chou, Sheng-Chieh (Thrombosis journal, 2025)
Thrombotic thrombocytopenic purpura (TTP) is an uncommon and life-threatening disorder caused by a deficiency of ADAMTS-13, and eventually leads to microangiopathic hemolytic anemia, severe thrombocytopenia, and organ damages. Acute TTP events could be triggered by infections, or inflammations in the context of ADAMTS-13 deficiency. Recently, several case reports have indicated an association between diabetic ketoacidosis (DKA) and TTP. Here, we present a case with the concomitant presentation of DKA and TTP. A 37-year-old male with diabetes mellitus presented with typical symptoms of diabetic ketoacidosis. He was managed with an insulin pump and intravenous fluids. However, he developed seizure and progressed to coma, his rapidly deteriorating condition necessitated continuous renal replacement therapy, intubation, and inotropic support. Laboratory data indicated hemolytic anemia and thrombocytopenia, and a blood smear revealed schistocytes. The PLASMIC score was 5, and ADAMTS-13 activity was 2%. The patient was diagnosed with TTP and treated with therapeutic plasma exchange, steroids, and rituximab. His platelet count stabilized above 150,000/µL, and ADAMTS-13 activity progressively improved. This case report emphasizes the concurrence of DKA and iTTP, presenting the rare complication of acute renal failure in TTP. TTP is a rare and serious disease that requires prompt recognition and management. Concurrent conditions should be considered when calculating prediction scores such as the PLASMIC and French scores.